2020
DOI: 10.1093/jbi/wbz093
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and Attitudes Regarding Adjunct Breast Cancer Screening Among Patients with Dense Breasts

Abstract: Objective New breast screening modalities are being investigated to address the need for more sensitive breast cancer screening in women with dense breasts. We investigated the preferences and attitudes of these patients regarding adjunct screening modalities to help evaluate the acceptability of these exams. Methods In this institutional review board–approved prospective study, patients with dense breasts on their prior mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Another key finding of our study was that younger patient age was the only predictor variable independently associated with concern about examination cost, which was by far the most common deterrent (66.9%) to adjunct screening [9].…”
Section: Accepted Manuscriptmentioning
confidence: 59%
See 4 more Smart Citations
“…Another key finding of our study was that younger patient age was the only predictor variable independently associated with concern about examination cost, which was by far the most common deterrent (66.9%) to adjunct screening [9].…”
Section: Accepted Manuscriptmentioning
confidence: 59%
“…A recent prospective survey of women with dense breasts who presented for screening mammography was conducted to better understand patient preferences and attitudes toward adjunct screening [9]. This study found that, while the majority of these patients (60%) felt that it was likely or very likely that breast cancer could be missed on their mammogram due to having dense breasts, a small percentage (9%) reported having undergone adjunct screening examinations within the preceding three years.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations